Hypertensive ulcer of lower extremity (Martorell’s syndrome): clinical case with the treatment improvement - Igor, Duzhiy; Vasyl, Popadynets; Andrii, Nikolaienko; Mykola, Lyndin; Vladyslav, Sikora (Bangladesh Journal of Medical Science, 2017)
Introduction. Martorells syndrome (MS) is a rare disease associated with chronic progressive hypertension which complicates ulcer defects on the extremities. It requests individual approach to treatment with antihypertensive medications, which help to reduce pathogenesis of the ulceration development. Therefore the aim of this study was to find new treatment methods of this disease. Case presentation. A 83-year-old female Ukrainian patient presented with an ulcer on the right calf, which was extremely painful at night. After all examination it was diagnosed: stage 2 hypertension, high risk, Martorells syndrome, right lower limb trophic ulcer of the hypertonic genesis. For the treatment of MS we used the combination therapy, which included tissue suturing on the whole area of the ulcer and auto-dermoplasty with PRP applications. After that was noted intense regenerative processes and recovery of the patient. Conclusions. Chronic leg ulcers are rarely caused by Martorells syndrome. It requires the complex approach to the treatment under obligatory antihypertensive therapy with its further prolongation. The complex therapy improved by the platelet-rich auto plasma activates the therapeutic effect, which results in intensive healing of the ulcer and faster improvement in pain relief. The platelet-rich auto plasma may become an economic method of treatment the ulcers of any genesis. Bangladesh Journal of Medical Science Vol.16(2) 2017 p.325-328